2007
DOI: 10.1002/ptr.2158
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the aqueous extract of Syzygium cumini on carbon tetrachloride‐induced hepatotoxicity in rats

Abstract: The aim of this study was to evaluate the effect of the aqueous Syzygium cumini leaf extract, given either as a single dose or by 7 days of pretreatment, on hepatotoxicity induced by carbon tetrachloride in rats. Blood samples obtained after treatments were measured for aspartate aminotransferase (AST) and alanine aminotransferase (ALT). A significant increase in the AST and ALT activities occurred after carbon tetrachloride administration alone, which was significantly lowered by preadministration with the aq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 8 publications
3
25
0
2
Order By: Relevance
“…The main compounds present in the ASc (gallic acid, chlorogenic acid and rutin) can be responsible for these effects, since they have been known by their antioxidant capacity. The protection effect of ASc observed in the present study is consistent with the beneficial results found by Stanley [75], Moresco [76] and Bopp [44].…”
Section: Discussionsupporting
confidence: 82%
“…The main compounds present in the ASc (gallic acid, chlorogenic acid and rutin) can be responsible for these effects, since they have been known by their antioxidant capacity. The protection effect of ASc observed in the present study is consistent with the beneficial results found by Stanley [75], Moresco [76] and Bopp [44].…”
Section: Discussionsupporting
confidence: 82%
“…66 The fruit extract of Jamun has also been reported to protect rat hepatocytes against carbon tetrachloride-induced toxicity in vitro. 30 Similarly, the administration of ethanol extract of Jamun fruit pulp for 8 consecutive days prior to paracetamol treatment has been shown to protect rats against paracetamol-induced hepatotoxicity.…”
Section: Hepatoprotective Activitymentioning
confidence: 99%
“…It has several medicinal properties. 5 The phenolic content of S. cumini leaves and antioxident activity were found high and the latter was comparable to ascorbic acid. 6 The presence of polyphenolic compounds in ethanolic leaf extract of S. cumini might be responsible for its high antioxidant activity.…”
Section: Introductionmentioning
confidence: 90%